2020
DOI: 10.3390/jcm9103183
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Association between Intraoperative Hypotension and Postoperative Neurocognitive Disorders in Non-Cardiac Surgery: A Comprehensive Review

Abstract: Postoperative delirium (POD) and postoperative cognitive decline (deficit) (POCD) are related to a higher risk of postoperative complications and long-term disability. Pathophysiology of POD and POCD is complex, elusive and multifactorial. Intraoperative hypotension (IOH) constitutes a frequent and vital health hazard in the perioperative period. Unfortunately, there are no international recommendations in terms of diagnostics and treatment of neurocognitive complications which may arise from hypotension-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Cerebral hypoperfusion occurring with or as a result of controlled hypotension seems inevitable. Surprisingly, no international recommendations or high quality evidence for diagnostics and treatment of neurocognitive impairment that may arise from hypotension-related hypoperfusion is available [16,17]. Consistent with this result, this study reported the reduction in L-SBP, M-SBP, and M-DBP in patients with severe POCD, but the differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 65%
“…Cerebral hypoperfusion occurring with or as a result of controlled hypotension seems inevitable. Surprisingly, no international recommendations or high quality evidence for diagnostics and treatment of neurocognitive impairment that may arise from hypotension-related hypoperfusion is available [16,17]. Consistent with this result, this study reported the reduction in L-SBP, M-SBP, and M-DBP in patients with severe POCD, but the differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 65%
“…However, it did not affect the occurrence of POD. Previous studies focusing on the relationship between intraoperative hypotension and POD had significant heterogeneity, thus generating conflicting results regarding the association between hypotension and POD [ 8 , 25 , 26 ]. Furthermore, although the exact mechanism of delirium is unclear, neuro-inflammation may play an important role in its development [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also revealed old age as a significant risk factor for PND. Older patients often have more neurovascular disease risk factors, more severe cerebral white matter injury, and less cognitive reserve than younger patients, and thus are at a higher risk of cognitive disorders after anesthesia and surgery ( 21 ). Multiple studies have identified diabetes, lower educational level, duration of surgery, and duration of ICU stay as significant risk factors for PND ( 21 – 23 ), but no correlation was noted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients often have more neurovascular disease risk factors, more severe cerebral white matter injury, and less cognitive reserve than younger patients, and thus are at a higher risk of cognitive disorders after anesthesia and surgery ( 21 ). Multiple studies have identified diabetes, lower educational level, duration of surgery, and duration of ICU stay as significant risk factors for PND ( 21 – 23 ), but no correlation was noted in the present study. This discrepancy may be attributable to the relatively small sample size and narrow differences in the duration of ICU stay, education background, and other aspects.…”
Section: Discussionmentioning
confidence: 99%